Educational interventions for diabetes prevention knowledge and behavior in children: a systematic review and meta-analysis - Mariana Ulfa; Okki Dhona Laksmita; Nur Agustini; Happy Hayati; Imamah Indah Cahyani; Mega Hasanul Huda (Universitas Gadjah Mada, 2026)
Purpose: This systematic review and meta-analysis evaluated educational interventions for improving type 2 diabetes prevention knowledge and preventive behaviors among children. Methods: A systematic search was conducted in PubMed, ScienceDirect, SAGE Journals, Scopus, ProQuest, MEDLINE, and the Cochrane Library for studies published between 2015 and 2025. Eligible studies were RCTs, cluster RCTs, and quasi-experimental studies evaluating diabetes prevention education among children aged approximately 6–18 years without diabetes and reporting knowledge or preventive behavior outcomes. Risk of bias was assessed using RoB 2 and ROBINS-I. Random-effects meta-analyses calculated standardized mean differences (SMDs) with 95% confidence intervals (CIs). Results: Thirteen studies were included; six were eligible for knowledge meta-analysis and four for preventive behavior meta-analysis, while the remaining studies were summarized narratively. Pooled analyses suggested that educational interventions were associated with improvements in diabetes prevention knowledge (SMD = 1.597; 95% CI: 0.796–2.398; p < 0.001) and preventive behaviors (SMD = 0.625; 95% CI: 0.162–1.089; p = 0.008). Interventions with more than four sessions and cluster RCTs appeared to show stronger effects. Substantial heterogeneity was observed, likely reflecting differences in study design, intervention duration, delivery methods, and outcome measures. Conclusion: Educational interventions appear to be associated with improved knowledge of type 2 diabetes prevention and may support preventive behaviors among children, but findings should be interpreted with caution given heterogeneity and methodological limitations. Multi-session school-based interventions, particularly those with more than four sessions, may be more promising. More rigorous studies with longer follow-up are needed.